2022
DOI: 10.1007/s10825-022-01957-y
|View full text |Cite
|
Sign up to set email alerts
|

Critical parameters of gate control in NC-FinFET on GaAs

Abstract: : Gate control ability is expected to keep constant, guaranteeing accurate MOSFET adjustment of drive strength by changing its size. In NCFET, the non-uniform distribution of ferroelectric polarization and capacitance match are sensitive to the size and tend to enhance the fluctuation of gate control. In the current work, a detailed simulation was made on NC-FinFET to clarify the effect of structural factors on its gate control. These factors include the Fin structure (length, width, and height), the doping co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Under alkaline conditions, the iron coagulant easily hydrolyzes to Fe(OH) 3 , and the negatively charged [Fe(OH) 4 ] À reduces the role of electric neutralization, adsorption bridging and net trapping and sweeping. 57,58 The result is a decrease in the removal effect of PS. In general, it showed that the change in floc densities at different pH also applies to the change in PS removal rate.…”
Section: Factors Impacting the Coagulation Effectmentioning
confidence: 99%
“…Under alkaline conditions, the iron coagulant easily hydrolyzes to Fe(OH) 3 , and the negatively charged [Fe(OH) 4 ] À reduces the role of electric neutralization, adsorption bridging and net trapping and sweeping. 57,58 The result is a decrease in the removal effect of PS. In general, it showed that the change in floc densities at different pH also applies to the change in PS removal rate.…”
Section: Factors Impacting the Coagulation Effectmentioning
confidence: 99%